Pathological review of primary cutaneous malignant melanoma by a specialist skin cancer multidisciplinary team improves patient care in the UK. Issue 7 (14th May 2019) - Bhoyrul, Bevin; Brent, Geoffrey; Elliott, Faye; McLorinan, Joanna; Wilson, Amy; Peach, Howard; Mathew, Bipin; Mitra, Angana
Abstract : Aims: The National Institute for Health and Care Excellence advocated the development of specialist skin cancer multidisciplinary teams (SSMDTs) for the management of higher risk invasive skin cancers in the UK. The interobserver variability in the histopathological assessment of primary cutaneous malignant melanoma (PCMM) is well recognised. Methods: We evaluated the discordance rates in the assessment of the histopathological criteria of PCMM based on the eighth American Joint Committee on Cancer (AJCC) melanoma staging system and subsequent change in prognosis and management following pathology review by an SSMDT. Results: 353 cases of PCMM were referred to our SSMDT between April 2015 and May 2016. Cases in which there was a discrepancy in one or more histological parameters following expert review were collected retrospectively. Of 341 eligible cases, there were 94 (27.6%) in which there was an alteration in any parameter. There was interobserver agreement in final diagnosis in 96.8%, Breslow thickness in 86.8%, ulceration in 98.2%, microsatellites in 98.5%, tumour mitotic rate in 88.9%, histological subtype in 92.4%, growth phase in 98.5%, angiolymphatic invasion in 97.7%, perineural invasion in 98.8%, regression in 95.3% and tumour-infiltrating lymphocytes in 95.0%. A corresponding change in AJCC stage occurred in 23 cases (6.7%), with a resulting change in clinical management in 10 cases (2.9%). Conclusions: Disagreements in the pathological assessment of PCMM can have significant clinical implications for a small number of patients. Our findings highlight the value of the SSMDT for high-quality care of patients with melanoma in the UK.